Towards a Dialogic Approach of Seeing in Art History and Visual Culture Studies (KULT_online, 2017)
The monograph Jenseits des Spiegels. Das Sehen in Kunstgeschichte und Visual Culture Studies is dedicated to the complex relationship between art history and visual-culture studies. With a discourse- and scientific-historical perspective on the act of seeing, identified as the overlapping moment of both disciplines, the art historian Susanne Falkenhausen examines the epistemological interests as well as the theoretical and methodological consequences by questioning canonical texts. The author advocates a dialogic approach to seeing in the process of interpretation – for an ethical dimension which not only maintains the tension between objectivity and subjectivity but also acknowledges the ‘otherness’ of the opposite entity.